Remote Method Invocation (RMI): A Review of the Literature (Innovation & Development in Engineering and Applied Science, 2023)
The review of the literature has been important to understand the occurrence of different studies on a specific topic and of interest to society, which is why it has been seen the need to carry out a literature review regarding the mechanism of invocation of remote methods. Remote Method Invocation (RMI) as such, is a technology used for communication between objects, a topic that has been particularly relevant in distributed computing and parallel processing, which has allowed the development of multiple business applications as well as games. . For this reason, having as a guide a methodology for the bibliographic review and the management of information on scientific topics that is based on centralizing a problem, searching for information and organizing information, it has begun by selecting a certain number of investigations to proceed with the literature review of in such a way that the most important concepts and contributions made in each of the investigations can be extracted. A list of topics that include RMI as the basis of study was made and the most relevant was searched for in principle an introduction regarding distributed computing, RMI and its form of implementation, in addition to making tables where the definitions of some authors are specified. , as well as the advantages and disadvantages of this technology in terms of its implementation and use in the area of ​​Computer Science.
Keywords: Java; remote method invocation; objects; parallel processing; distributed systems